Weyl Almost Periodic Solutions in Distribution of Clifford-Valued Stochastic High-Order Hopfield Neural Networks with Delays on Time Scales (CSIAM Transactions on Applied Mathematics, 2022)
In this paper, we first propose a concept of Weyl almost periodic randomprocesses on time scales, including the concepts of Weyl almost periodic random processes in $p$-th mean and Weyl almost periodic random processes in distribution. Then,using the Banach fixed point theorem, time scale calculus theory and inequality techniques, the existence and stability of Weyl almost periodic solutions for Clifford-valuedstochastic high-order Hopfield neural networks with time-varying delays on time scalesare studied. Even when the system we consider degenerates into a real-valued system,our results are new. Finally, a numerical example is given to illustrate the feasibility ofour theoretical results.